THE IMPORTANCE OF VISIBILITY IN TEACHING MATHEMATICAL REASONING PROBLEM SOLVING - Munisa Aminovna Davlatova (European Science Publishing, 2024)
This article is written about improving students' knowledge, skills and abilities in solving logical problems in elementary mathematics classes. course, a demonstrative method of solving logical problems is considered. Differences in working on some issues in the upper class and in the primary class are shown.
Keywords: mathematics, problem, practical, ability, thinking, skill.